Automated quality assurance of HDR brachytherapy: Evaluation of Dwell‐position accuracy and Dwell‐time linearity via image processing of radiochromic films. - Yuan, Qingqing; Bi, Suyan; Lou, En; Jia, YaJun; Dai, Zhitao (Precision Radiation Oncology, 2026)
Purpose: To develop and validate a fully automated quality assurance method for high‐dose rate (HDR) brachytherapy, enabling the precise evaluation of source dwell‐position accuracy and dwell‐time linearity using radiochromic film analysis and advanced image processing algorithms. Methods: A novel analytical framework was established to verify HDR source positional precision and dwell‐time linearity. Radiochromic films were irradiated under predefined treatment plans. Image preprocessing involved grayscale conversion, median filtering, rotation correction, and absolute coordinate calibration. The centroid of each dwell position was determined using two‐dimensional Gaussian fitting. Temporal linearity analysis employed radial grayscale summation within the radii of 250–400 pixels. Linearity was quantified using the coefficient of determination (R2), with R2 approaching 1 indicating optimal performance. Results: Automated Gaussian fitting achieved sub‐millimeter positional accuracy (maximum error ≤ 0.6 mm), eliminating manual intervention. Rotation correction algorithms effectively mitigated positional errors caused by film misalignment. Comparative analysis with commercial software yielded nearly identical results, validating the reliability of the method. Dwell‐time analysis demonstrated excellent linearity (R2≥0.999) over summation radii ranging from 150 to 400 dpi. Conclusions: This study presents a robust and fully automated quality assurance (QA) solution for HDR brachytherapy that simultaneously verifies sub‐millimeter‐level dwell‐position accuracy and temporal linearity. The integration of radiochromic film dosimetry with algorithmic image processing eliminates manual intervention and standardizes QA workflows, representing a substantial advancement in treatment safety and efficiency.